Victim Empathy Intervention With Sexual Offenders: Rehabilitation, Punishment, or Correctional Quackery?. (June 2013) - Mann, Ruth E.; Barnett, Georgia D.
A sexual offender is thought to have victim empathy when he has a cognitive and emotional understanding of the experience of the victim of his sexual offense. Most sex offender treatment programs devote significant time to developing victim empathy. The authors examine three meta-analytic studies and some individual studies that suggest victim empathy work is unnecessary, or even harmful. Service user studies, however, report positive reactions to victim empathy work. The authors conclude that the enthusiasm for victim empathy work as a rehabilitative endeavor is disproportionate given the weak evidence base and the lack of a coherent theoretical model of change. However, because the research is inconclusive, it is not possible to conclude that victim empathy work is "correctional quackery." We suggest a research program to clarify whether or not victim empathy intervention for sexual offenders has value.